Evalution of Antibacterial and Antioxidant Activity of Methanolic and Hydromethanolic Extract of Sweet Orange Peels - Agrawal1, Rahul Verma1 and Rahi Jain1, Dayanand Dubey1*, K. Balamurugan2, R.C. (Recent Research in Science and Technology, 2011)
The in vitro antibacterial and antioxidant properties of hydromethanolic extract of peel from Citrus sinensis (Sweet orange) was investigated. In this study the antibacterial activity of Citrus sinensis peel extract against different gram positive and gram negative bacteria by disc diffusion method and antioxidant activity by Fenton reaction was undertaken. Citrus sinensis peels had shown mild activity against gram positive and gram negative bacteria and the MIC value was measured. In another experiment antioxidant activity was observed and IC50 was shown at 600 Ã‚Âµg/ml.